Zaangażowanie, unikanie, odmowa współpracy. Marian Jurczyk wobec Służby Bezpieczeństwa (1977–1980) - Michał Siedziako (Kwartalnik Historyczny)
This article discusses the rela tionship of one of the later leaders of the „Solidarity” Trade Union, Marian Jurczyk, with the Security Service, during the 1970s. At that time, the political police were mon itoring the milieu of former strike activists from December 1970 to January 1971 in the Szczecin Shipyard, including Jurczyk. As part of this surveillance, information was collected on individuals and eff orts were made to control their actions against the prevailing political realities. Jurczyk was recruited for collaboration in 1977, and he actually ended it in 1979. The last attempt to get his cooperation was made when he led the strikes in Szczecin in the summer of 1980, but he refused and was de-registered from the Security Service’s lists of collaborators in 1981